Developmental symbiosis facilitates the multiple origins of herbivory. Issue 1 (22nd July 2019) - Gilbert, Scott F.
Abstract: Developmental bias toward particular evolutionary trajectories can be facilitated through symbiosis. Organisms are holobionts, consisting of zygote‐derived cells and a consortia of microbes, and the development, physiology, and immunity of animals are properties of complex interactions between the zygote‐derived cells and microbial symbionts. Such symbionts can be agents of developmental plasticity, allowing an organism to develop in particular directions. This plasticity can lead to genetic assimilation either through the incorporation of microbial genes into host genomes or through the direct maternal transmission of the microbes. Such plasticity can lead to niche construction, enabling the microbes to remodel host anatomy and/or physiology. In this article, I will focus on the ability of symbionts to bias development toward the evolution of herbivory. I will posit that the behavioral and morphological manifestations of herbivorous phenotypes must be preceded by the successful establishment of a community of symbiotic microbes that can digest cell walls and detoxify plant poisons. The ability of holobionts to digest plant materials can range from being a plastic trait, dependent on the transient incorporation of environmental microbes, to becoming a heritable trait of the holobiont organism, transmitted through the maternal propagation of symbionts or their genes. RESEARCH HIGHLIGHTS: The concept that developmental bias can influence evolution is fulfilled when one perceives the organism as a holobiont and views development as a multi‐species process. For herbivory to originate, animals need to obtain the proteins needed to digest plant cell walls. This can occur through the acquisition of microbes through symbiosis or through the acquisition of such genes by lateral gene transmission from such herbivorous microbes. In many instances, the microbes construct niches in the developing organism.